The misfortunate elites with a mirage: F. Scott Fitzgerald shaping modern human in This Side of Paradise and The Great Gatsby - Awal, Nafisa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.